A qualitative investigation on consumer trust in mobile commerce. (7th September 2004) - Siau, Keng; Sheng, Hong; Nah, Fiona; Davis, Sid
Mobile commerce represents a significant development in e-commerce, offering accessibility, ubiquity, mobility, and localisation to users. Despite the potential of mobile commerce, trust is a major obstacle in its adoption and development. Many consumers feel uncomfortable with the idea of conducting commerce over wireless, hand-held devices. The focus of this research is to understand trust in mobile commerce and to identify factors that are important for trust development. The research builds on Siau and Shen's framework which depicts two key factors influencing trust in mobile commerce. This research not only validates and expands on the existing framework, but also provides an expanded conceptual model for future research.